Oral manifestation of aspergillosis in an immunocompetent child: case report - Angarani, Germano; Cunha, Laryssa Queiroz; Paula, Laiz Moreira; Brito, Lucas Teixeira; Prata-Júnior, Agnaldo Rocha; Silveira, Rubens Jorge (Journal of Oral Diagnosis, 2020)
Fungi is a kingdom present in nature that has low virulence, occasionally they are capable of causing diseases when there is a commitment on host’s defenses. There are reports of in- creased incidence of the disease in immunocompetent patients; however, oral manifestations are rare. A 5-years-old male patient was referred to the Maxillofacial Surgery service for evaluation of a vegetating, sessile a vascularized lesion with granulomatous areas, without reports of systemic changes. Computed tomography showed mucosal thickening in the associated maxillary sinuses and area of bone erosion on the floor of the left nasal cavity, and after that, incisional biopsy was performed obtaining the diagnosis of aspergillosis. Hospitalization of the patient was necessary and the treatment with intravenous liposomal amphotericin B and oral Voriconazole lasted six weeks, successfully treating disease and remitting the lesion. Since then, patient remains asymptomatic and without signs of the disease after 3 months of hospital discharge. The authors emphasize the importance of early diagnosis and the appropriate antifungal agents selection for successful treatment.